2019
DOI: 10.1128/iai.00642-18
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Nutritional Immunity and Independent Host Defenses Contributes to the Importance of the MntABC Manganese Transporter during Staphylococcus aureus Infection

Abstract: During infection, the host utilizes a diverse array of processes to combat invaders, including the restriction of availability of essential nutrients such as manganese. Similarly to many other pathogens, Staphylococcus aureus possesses two manganese importers, MntH and MntABC. Several infection models have revealed a critical role for MntABC during staphylococcal infection. However, culture-based studies have suggested parity between the two transporters when cells are resisting manganese starvation imposed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 87 publications
(189 reference statements)
3
36
0
Order By: Relevance
“…While evidence showing a major reduction in the levels of intracellular Mn pools and the most severe phenotypes was restricted to the ΔsloC ΔmntH double mutant, deletion of sloC alone significantly impaired growth of S. mutans in the chemically defined media lacking both Mn and Fe as well as in the presence of calprotectin. This finding is in agreement with previous observations made with S. aureus showing that the staphylococcal SloABC homologue, named MntABC, was more important than MntH during infection and that loss of mntABC alone resulted in a virulence defect (45). The apparent more prominent role of SloABC than of MntH seen under these specific conditions is likely due to its dual function in Fe and Mn uptake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While evidence showing a major reduction in the levels of intracellular Mn pools and the most severe phenotypes was restricted to the ΔsloC ΔmntH double mutant, deletion of sloC alone significantly impaired growth of S. mutans in the chemically defined media lacking both Mn and Fe as well as in the presence of calprotectin. This finding is in agreement with previous observations made with S. aureus showing that the staphylococcal SloABC homologue, named MntABC, was more important than MntH during infection and that loss of mntABC alone resulted in a virulence defect (45). The apparent more prominent role of SloABC than of MntH seen under these specific conditions is likely due to its dual function in Fe and Mn uptake.…”
Section: Discussionsupporting
confidence: 92%
“…Though the enzyme is cambialistic (capable of using either Mn or Fe), studies have shown that the Mn-bound SOD is much more active than Fe-bound SOD (63). Evidence has suggested that restriction of the Mn-dependent SOD by metal sequestration is an important aspect of the contribution of calprotectin to nutritional immunity for S. aureus pathogenesis and that the staphylococcal MntH and MntABC manganese transporters are critical for infection (45,58).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the effect of CP on iron uptake by S. aureus varies tremendously depending on the medium because extensive inhibition of iron uptake by S. aureus was observed in LB, whereas negligible change occurred in Tris/TSB. Along these lines, metal inventory data from studies of the competition between CP and S. aureus showed that CP only reduced manganese acquisition by S. aureus strain Newman following growth in TSB or Tris/TSB (20,50). Taken together, these data indicate the importance of considering the effect of growth conditions on bacterial metabolism in studies of CP and, more broadly, nutritional immunity.…”
Section: Calprotectin Induces Iron Starvation In P Aeruginosamentioning
confidence: 86%
“…Deletion of these genes did not affect growth in metal sufficient media (38). μg/mL adenine) and 62% calprotectin buffer (20 mM Tris pH 7.5, 100 mM NaCl, 3 mM CaCl 2 ), and 0-240 μg/mL recombinant calprotectin (65,91). At 8 hours post-inoculation, growth was assessed by measuring optical density (OD 600nm ) and plating serial dilutions to quantitate CFU.…”
Section: Bacterial Strains and Growth Conditions Streptococcus Agalamentioning
confidence: 99%